Quasi-torpor for long-duration space missions - Weissman, Alexandra J.; Flickinger, Katharyn L.; Wu, Victor; DeMaio, Ryann; Jonsson, Andrea; Prescott, Peter; Monteleone, Jenna; Zurowski, Emma; Guyette, Francis Xavier; Gordon, Benjamin D. H.; Mortreux, Marie; Melanson, Kathleen; et al. (Frontiers in Space Technologies, 2024)
Abstract Innovative solutions are required to make long-duration space missions feasible. Crew performance and health is paramount to the success of anticipated Moon and Mars missions. Metabolic reduction via a quasi-torpor state is a possible mitigation strategy that can reduce consumable payload, which is necessary given the lack of available resupply options, and to reduce psychological stress, which is a risk for such lengthy missions. Even in lunar or cis-lunar missions, a quasi-torpor state could be implemented as an emergency countermeasure for critical situations where life support becomes limited. However, to date no studies have tested a quasi-torpor state in humans, and the impacts of intentional prolonged metabolic reduction on physiological and psychological parameters are unknown. To this end, we planned a three-phase study to provide proof-in-principle of the tolerability, feasibility, and side effects of a non-intravenous alpha-2-adrenergic receptor agonist for moderate sedation. This was accomplished by 1) determining the dosing and metabolic effects for different non-intravenous routes of alpha-2-adrenergic receptor agonist drugs; 2) assessing the degree of metabolic reduction and side effects during a 24-hour quasi-torpor protocol; and 3) evaluating participant performance and total metabolic reduction achieved over a five-day quasi-torpor protocol. We also aim to determine how skeletal muscle health and performance are affected by this quasi-torpor state. Quasi-torpor induced changes in skeletal muscle health and performance, as well as impacts on cognition and psychological stress, also have implications for terrestrial situations that result in prolonged confinement (e.g., austere environments such as submarine or remote scientific or military deployment and protracted critical illness). The findings of this three-phase study will be immediately applicable as a rescue strategy for emergencies during current or upcoming space missions. They will also identify key physiological and practical questions that need to be addressed for future deployment in long-duration space missions. This paper reviews the relevant literature that informed our rationale and approaches for this three-phase study.